2020
DOI: 10.1097/scs.0000000000006965
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Dressing Fixation Method Following Harvest of the Ear Cartilage Graft

Abstract: The blood supply from the BFP comes from branches of the internal maxillary, superficial temporal, and facial arteries. This complication may be associated with deep dissection of the oral space or a vascular avulsion injury from traction on the BFP. If local measures such as compression and blood vessel suture fail to achieve hemostasis, other methods to stop bleeding should be adopted immediately to prevent further severe complications that can be life-threatening. 13,14 Careful removal of this structure sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In contrast, our study used only a retroauricular approach, so skin discoloration was not an issue. In 2021, Du et al 26 reported using the simple dressing-fixation method following cartilage harvest and obtained a result similar to ours, with a possible complication from the bolster dressing. One patient presented with a concha bowl defect from pressure necrosis due to prolonged pressure from the bolster dressing.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, our study used only a retroauricular approach, so skin discoloration was not an issue. In 2021, Du et al 26 reported using the simple dressing-fixation method following cartilage harvest and obtained a result similar to ours, with a possible complication from the bolster dressing. One patient presented with a concha bowl defect from pressure necrosis due to prolonged pressure from the bolster dressing.…”
Section: Discussionsupporting
confidence: 81%
“…Its advantages are as follows: (1) relatively easy harvesting technique(s), (2) fewer surgical scars, (3) a short operative time, and (4) relatively few or no serious complications. Two techniques exist for harvesting the concha cartilage: the anterior approach 22 , 23 and the posterior or retroauricular approach 10 , 24 - 26 . Of these, the anterior approach is easier because it allows direct visualization of all anatomical boundaries.…”
Section: Discussionmentioning
confidence: 99%